Oral amoxicillin versus intravenous ampicillin for chest indrawing pneumonia in children aged 3–59 months: A randomized control trial - Gokilavani, Mahendran; Naaraayan, Sridevi A; Priyadharishini, Dorairaj; Begum, Najumudeen Shajathi (Indian Journal of Child Health, 2020)
Background: Pneumonia is one of the leading causes of under-five mortality. There is lack of consistency in treatment guidelines issued by various organizations. Objective: The primary objective of the study was to compare the efficacy of oral amoxicillin against intravenous (IV) ampicillin in children aged 3–59 months with chest retraction pneumonia. The secondary objective was to identify the risk factors associated with the absence of clinical improvement at the end of 48 h of treatment. Materials and Methods: This was a non-blinded randomized controlled, non-inferiority trial of oral amoxicillin 80 mg/kg/day in two divided doses and IV ampicillin 200 mg/kg/day in three divided doses in children aged 3–59 months with chest retraction pneumonia. The study was conducted in the pediatric wards of a tertiary care facility from November 2016 to September 2017. The children were followed up after 48 h and 5 days for the clinical improvement. The primary outcome considered was absence of improvement or deterioration in the study children at the end of 48 h of initiation of therapy and was expressed as risk difference between the two treatment groups. Multivariate regression analysis was performed to determine the predictors of poor outcome of the disease. Results: Risk difference of treatment failure between both groups was -3.7% (95% confidence interval [CI] ?16.8%–9.4%). The presence of wheeze and X-ray findings of pneumonia was significant independent risk factors for poor outcome at the end of 48 h. Conclusion: Oral amoxicillin is not inferior to IV penicillin in the treatment of chest retraction pneumonia in children aged 3–59 months. The presence of wheeze and X-ray findings suggestive of pneumonia can be used as prognostic indicators in children.